2013
DOI: 10.1371/journal.pone.0060908
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Signal Peptidase Complex Member Spase12 Is Required for Development and Cell Differentiation

Abstract: It is estimated that half of all proteins expressed in eukaryotic cells are transferred across or into at least one cellular membrane to reach their functional location. Protein translocation into the endoplasmic reticulum (ER) is critical to the subsequent localization of secretory and transmembrane proteins. A vital component of the translocation machinery is the signal peptidase complex (SPC) - which is conserved from yeast to mammals – and functions to cleave the signal peptide sequence (SP) of secretory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…This complex contains four subunits and has been found to be involved in the initiation of protein translocation (Fons et al, 2003), as well as the accelerated degradation of misfolded proteins (Nagasawa et al, 2007). A transmembrane signal peptidase (SP) and oligosaccharyltransferase (OST) complex is involved in cleaving off the signal peptide of proteins and to glycosylate the polypeptide, respectively (Mohorko et al, 2011;Haase Gilbert et al, 2013). One of the subunits of the SP complex has been newly identified in this study (Contig2157), as well as four subunits of the OST complex (Contig5725, 1356, 4332 and 1719) ( Table 2) which were, however, all previously identified in other publications in R. microplus in addition to R. sanguineus and Ornithodoros moubata for Contigs4332 and 1719 (Diaz-Martin et al, 2013;Oliveira et al, 2013).…”
Section: Proteins Involved In Protein Translocation and Modificationmentioning
confidence: 99%
“…This complex contains four subunits and has been found to be involved in the initiation of protein translocation (Fons et al, 2003), as well as the accelerated degradation of misfolded proteins (Nagasawa et al, 2007). A transmembrane signal peptidase (SP) and oligosaccharyltransferase (OST) complex is involved in cleaving off the signal peptide of proteins and to glycosylate the polypeptide, respectively (Mohorko et al, 2011;Haase Gilbert et al, 2013). One of the subunits of the SP complex has been newly identified in this study (Contig2157), as well as four subunits of the OST complex (Contig5725, 1356, 4332 and 1719) ( Table 2) which were, however, all previously identified in other publications in R. microplus in addition to R. sanguineus and Ornithodoros moubata for Contigs4332 and 1719 (Diaz-Martin et al, 2013;Oliveira et al, 2013).…”
Section: Proteins Involved In Protein Translocation and Modificationmentioning
confidence: 99%
“…As was observed with LmSPC1, obvious moulting defects occurred when genes related to the components of the secretion machinery of this process were inactivated (Frand et al ., ). The crippled wings observed after moulting in RNAi‐injected locust nymphs are similar to those observed in Drosophila with mutated Spase12, another subunit of the ER type I signal peptidase (Gilbert et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A vertebrate has more than 100 different types of cells, and many cells form very organized patterns to perform their specialized functions (Lodish et al ., ). However, the functions of ER type I signal peptidases in animals have only been described in the animal model Drosophila ; in these organisms, the subunit Spase12 was disrupted (Gilbert et al ., ), but essential catalytic subunits were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila melanogaster , four signal peptidase genes exist: Spase12 , Spase18/21 , Spase22/23 , and Spase25 (Abrams & Andrew, ). In Drosophila , a loss‐of‐function assay of Spase12 demonstrated that this gene causes defects in all of the tissues tested (Haase Gilbert, Kwak, Chen, & Mardon, ). In Drosophila , cell differentiation in the eyes was flawed if Spase12 was lost.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether there is any change with the adult midgut development if Spase18/21 was knocked down. Melanotic masses were observed in Spase12 mutant flies (Haase Gilbert et al., ), indicating that the loss of Spase12 likely activates the immune response pathway. Besides the studies as described above, we do not know the function of SPC in other insects including their importance to development.…”
Section: Introductionmentioning
confidence: 99%